Kebahagiaan Hati dengan Metode Tasawuf Perspektif Imam Al-Ghazali - Indry Nirma Yunizul Pesha; Nurlaela Sa’dillah; As’ad Rasyiq Haidar (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Happiness is the primary goal of human life. Imam Al-Ghazali, a prominent Sufi scholar, explains that true happiness can only be attained through a Sufi (tasawuf) approach, namely the purification of the heart and drawing closer to Allah. This study aims to analyze the concept of happiness from Al-Ghazali’s perspective and the Sufi methods he proposes to achieve it. The research employs a literature review method with a descriptive-analytical approach to Al-Ghazali’s works. The findings indicate that true happiness is attained through controlling one’s desires, purifying the heart, and complete submission to Allah. Furthermore, the five main Sufi methods taught by Al-Ghazali—repentance (taubah), asceticism (zuhud), patience (sabr), gratitude (shukr), and love (mahabbah)—are proven to be relevant in addressing various spiritual and psychological challenges faced by modern humans. The application of these methods can help individuals manage stress, improve mental health, and foster more harmonious social relationships. Therefore, this study affirms that Imam Al-Ghazali’s Sufi approach can serve as a solution for individuals seeking true happiness amid a life full of pressure and challenges.